Regional Financial Conglomerates : A Case for Improved Supervision - Olafsson, Thorvardur Tjoervi (IMF Working Papers; Working Paper ;, 2005)
The paper's central theme is that where a financial crisis emerges, regional supervisors should have systems in place to effectively respond to their country-specific crises and-in the case of foreign operations and financial conglomerates-to collaborate comprehensively with other supervisory agencies and respective ministries to avert a regional crisis or address the immediate crisis at hand. For financial institutions to expand across borders without undermining regional and global financial stability, supervisory agencies must develop the capacity to collaboratively and collectively handle crises.